Recycling of cathode from spent lithium iron phosphate batteries - Yadav, Prasad (2021)
We demonstrate the concept of fabricating new lithium ion batteries from recycled spent 18650 lithium ion batteries (LIB). LiFePO4 cathode was extracted from these spent LIB using combined approach of pre-treatment, mechanical treatment and hydrometallurgical process wherein weak organic acids, such as methyl sulfonic acid (MSA) and p-toluene sulfonic acid (TSA), were employed for the first time for leaching at room temperature of metal ions instead of conventional strong acids. High leaching efficiencies (95%) were obtained for extraction of Li and Fe using these acids from black mass. Reuse of these extracted metal ions is also demonstrated by precipitating them and synthesizing LiFePO4 cathode. Structural characterization showed the formation of single-phase LiFePO4 and electrochemical evaluation of this cathode in a LiFePO4/Li half-cell exhibited a capacity of 93 mA h/g and 80 mA h/g at 0.2C and 1C rate respectively with good cycle stability.